2011
DOI: 10.3109/13685538.2011.606514
|View full text |Cite
|
Sign up to set email alerts
|

Mild thyroid hormone excess is associated with a decreased physical function in elderly men

Abstract: Introduction In the adult, subclinical hyperthyroidism (Shyper) may alter skeletal muscle mass and strength. However, whether these effects are present in elderly subjects is not known. We explored the relationship between mild hyperthyroidism and physical function in a population-based sample of older persons. Methods In a cross-sectional analysis, calf muscle cross-sectional area (CMA), handgrip strength, nerve conduction velocity (NCV), and Short Physical Performance Battery (SPPB) scores were compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Similar findings had been reported by van den Beld et al who noted that in euthyroid men aged 73-94 years, higher serum FT4 concentrations were associated with reduced physical function, while low serum FT4 was associated with better 4-year survival (77). Interesting data came from a study by Ceresini and coworkers who evaluated the relationship between physical function and thyroid hormones in a large cohort of independently living ≥65 years subjects (78). In the study population, the authors measured muscle strength and mass and physical performance, all parameters that are closely related to frailty.…”
Section: Thyroid Status Morbidity and Mortality In The Elderlymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings had been reported by van den Beld et al who noted that in euthyroid men aged 73-94 years, higher serum FT4 concentrations were associated with reduced physical function, while low serum FT4 was associated with better 4-year survival (77). Interesting data came from a study by Ceresini and coworkers who evaluated the relationship between physical function and thyroid hormones in a large cohort of independently living ≥65 years subjects (78). In the study population, the authors measured muscle strength and mass and physical performance, all parameters that are closely related to frailty.…”
Section: Thyroid Status Morbidity and Mortality In The Elderlymentioning
confidence: 99%
“…On this evidence, frail individuals who suffer from weight loss and reduced lean mass, appear to be particularly at risk of overtreatment among older people, and thyroid hormone excess may have negative consequences beyond the well-known adverse effects, contributing to the pathogenesis of frailty itself. Indeed, besides lowering TSH, thyroid replacement therapy excess affects serum FT4 levels, which are independent predictors of frailty (68,70,77,78). Several studies have demonstrated that patients under l-T4 therapy have higher levels of FT4 than controls, even if within normal values, and serum FT4 concentrations are often at the upper limits of normal range (27,45).…”
Section: Replacement Therapy With Levothyroxine (L-t4): Benefits and mentioning
confidence: 99%
“…[146] explored the relationship between mild hyperthyroidism and physical function in the elderly. The first part of the study was a cross-sectional analysis in the InCHIANTI Study, in which several parameters of physical function were compared between 364 Eut men and 28 Shypert men and between 502 Eut and 39 Shypert women.…”
Section: Thyroid Hormones and Mobilitymentioning
confidence: 99%
“…The second part of the study was a longitudinal analysis, in which the authors evaluated the relationship between TSH, FT3 and FT4 and 3-year change in SPPB score in 304 men and 409 women who were Eut at enrolment. The analysis showed that in Eut men higher baseline FT4 was a significant independent predictor of steeper decline in SPPB score during 3-year follow-up period (P=0.02) [146]. …”
Section: Thyroid Hormones and Mobilitymentioning
confidence: 99%
See 1 more Smart Citation